Efeitos da exposição à sílica sobre a responsividade vascular e de vias aéreas de ratos - Bueno, Flávia Regina [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Silicosis, a common type of pneumoconiosis, is an occupational lung disease caused by inhalation of silica dust often with mining activity and thus reaches the miners. The fine and ultrafine silica particles deposited in the alveolar epithelium may lead to the development of progressive massive fibrosis. An increased reactive oxygen species (ROS) production has been proposed to explain the mechanism for induction of pulmonary fibrosis in silicosis. In this situation, alveolar macrophages are activated to phagocytes silica particles deposited in the alveoli. The activated macrophages secrete large amounts of ROS that in turn induce synthesis of fibrotic factors. In addition, the activity of antioxidant enzymes is impaired, which results in increased lipid peroxidation, as well as generating a local inflammatory process. Diffuse pulmonary fibrosis progresses with interstitial collagen deposition. Interstitial collagen overlies small pulmonary arteries and arterioles and thus it is associated with pulmonary hypertension in pulmonary fibrotic diseases. In addition, cytokines and silica particles passing through the respiratory membrane can reach the bloodstream. In this context, the increase in the generation of ROS in the circulation may lead to a reduction in the bioavailability of nitric oxide, an important endothelium-derived relaxing factor. A deficiency in the nitric oxide bioavailability can result in vascular endothelial dysfunction. Moreover, pro-inflammatory cytokines could contribute to the impairment of endothelial function. In the airways, pro-inflammatory cytokines can reduce the smooth muscle responsiveness to β- adrenergic agonists as isoproterenol. Thus, the aim of this study was to evaluate the effect of silica dust instillation in the function of the pulmonary artery, aorta and trachea of rats with acute silicosis. For this purpose, male Wistar rats were anesthetized... (Complete abstract click electronic access below)

A silicose, um tipo comum de pneumoconiose, é uma doença pulmonar ocupacional causada por inalação de sílica muitas vezes em pedreiras com atividade extrativista e atinge assim os mineradores. As partículas de sílica depositadas no epitélio alveolar podem ocasionar o desenvolvimento de fibrose maciça progressiva. Um aumento da produção de radicais livres tem sido uma das propostas para explicar o mecanismo para indução da fibrose pulmonar na silicose. A deposição de partículas de sílica nos alvéolos pulmonares induz a fagocitose dos mesmos pela ação de macrófagos residentes alveolares; estes, quando ativados, liberam grandes quantidades de espécies reativas de oxigênio (ERDOs). A capacidade de varredura de enzimas oxidantes locais é prejudicada, o que resulta em maior peroxidação lipídica, além da geração de um processo inflamatório local. A fibrose difusa cursa com deposição de fibras colágenas por todo o parênquima pulmonar, o que por sua vez pode suprimir pequenas artérias e arteríolas pulmonares e assim estar correlacionada com o desenvolvimento de hipertensão pulmonar. Além disso, citocinas e partículas de sílica que atravessam a membrana respiratória podem atingir a circulação sanguínea. Um aumento na geração de ERDOs na circulação pode levar a uma redução na biodisponibilidade do óxido nítrico (NO), um importante vasodilatador produzido e liberado pelo endotélio vascular. Uma relativa deficiência na quantidade de NO vascular disponível pode resultar em disfunção endotelial. Já um aumento de citocinas pró-inflamatórias pode contribuir para o desenvolvimento e/ou agravamento da disfunção endotelial. Nas vias aéreas, sabe-se que citocinas pró-inflamatórias podem causar redução da responsividade da via β-adrenérgica em células musculares lisas isoladas de vias aéreas de humanos. Assim, o objetivo deste trabalho.. (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Silica; Patologia; Arteria pulmonar; Endotelio; Oxido nitrico